News media, asset prices and capital flows: evidence from a small open economy - Sher, Galen (Division of Actuarial Science, 2017)
Objectives: This work investigates the role for the content of print news media in determining asset prices and capital flows in a small open economy (South Africa). Specifically, it examines how much of the daily variation in stock prices, bond prices, trading volume and capital flows can be explained by phrases in the print news media. Furthermore, this work links such evidence to the existing theoretical and empirical literature. Methods: This work employs natural language processing techniques for counting words and phrases within articles published in national newspapers. Variance decompositions of the resulting word and phrase counts summarise the information extracted from national newspapers in this way. Following previous studies of the United States, least squares regression relates stock returns to single positive or negative 'sentiment' factors. New in this study, support vector regression relates South African stock returns, bond returns and capital flows to the high-dimensional word and phrase counts from national newspapers. Results: I find that domestic asset prices and capital flows between residents and non-residents reflect the content of domestic print news media. In particular, I find that the contents of national newspapers can predict 9 percent of the variation in daily stock returns one day ahead and 7 percent of the variation in the daily excess return of long-term bonds over short-term bonds three days ahead. This predictability in stocks and bonds coincides with predictability of the content of domestic print news media for net equity and debt portfolio capital inflows, suggesting that the domestic print news media affects foreign residents' demand for domestic assets. Moreover, predictability of domestic print news media for near future stock returns is driven by emotive language, suggesting a role for 'sentiment', while such predictability for stock returns further ahead and the premium on long-term bonds is driven by non-emotive language, suggesting a role for other media factors in determining asset prices. These results do not seem to reflect a purely historical phenomenon, finite-sample biases, reverse causality, serial correlation, volatility or day-of-the-week effects. The results support models where foreign agents' short-run beliefs or preferences respond to the content of domestic print news media heterogeneously from those of domestic agents, while becoming more homogeneous in the medium term.